New transnationalisms in contemporary Latin American cinemas - Tierney, Dolores (Traditions in world cinema., 2018)
In the late 1990s and early 2000s Latin American films like Amores perros, Diarios de motocicleta, Y tu mamá también and Cidade de Deus enjoyed an unprecedented level of critical and commercial success in global markets. Benefiting from external financial and/or creative input, these films were considered examples of transnational cinema. Through a textual analysis of six filmmakers (Alejandra González Iñárritu, Alfonso Cuarón, Guillermo del Toro, Fernando Meirelles, Walter Salles and Juan José Campanella), this book examines these and other transnational films including the subsequent wave of commercially successful 'deterritorialised' films by the same directors. It argues that although the films produced within the parameters of the United States film industry may have been commercially successful, they are not necessarily apolitical nor totally divorced from key notions of national or continental identity. Bringing a new perspective to the films of Latin America's transnational auteurs, New Transnationalisms in Contemporary Latin American Cinemas is a major contribution towards understanding how different genres function across different cultures--back cover.